Obtaining Ion Exchangers Based On Acrylonitrile By Granular Polymerization - Bobylova Chinnigul Khaitovna (Research Parks Publishers, 2022)
Research on the improvement of methods for the synthesis of ion-exchange sorbents with a porous structure based on copolymers is relevant.